Menggali Pendidikan Karakter Anak “Perspektif R.A. Kartini” - Manijo, Manijo (PIAUD Universitas Islam Negeri Sunan Kudus, 2013)
There is still an urgent figure of RA Kartini reviewed and used as a historical reference. It is interesting to know the background of her family situation, social, and religious conditions of RA Kartini during her lifetime so that all make her to be the ideal figure, a woman whose had strong spirit at her time, dynamic, and be independent, high intellectual, modern -minded, also had social sensitivity and a spirit of nationalism and a sense of God. Due to her thought and struggle, she labels as an Indonesian women movement pioneer, an intellectual, an educator, a journalist, and a social worker. RA Kartini’s biography shows a lot of factors that affect their lives, including her thoughts. By analyzing her historical life, there are some character building factors that can be uploaded in children education nowadays, namely: strong, smart, and religious. Critical social character, educator character, and social character with a progressive vision are what began to disappear in today children education. RA Kartini’s character building can be used as a reference for Indonesian to build a strong and visionary one, that can be started from the base of Raudhotul Atfal Teacher Education (PGRA).